TRPV1 and BDKRB2 receptor polymorphisms can influence the exercise pressor reflex - Notay, Karambir (J Physiol, 2018)
KEY POINTS: The mechanisms responsible for the high inter‐individual variability in blood pressure responses to exercise remain unclear. Common genetic variants of genes related to the vascular transduction of sympathetic outflow have been investigated, but variants influencing skeletal muscle afferent feedback during exercise have not been explored. Single nucleotide polymorphisms in TRPV1 rs222747 and BDKRB2 rs1799722 receptors present in skeletal muscle were associated with differences in the magnitude of the blood pressure response to static handgrip exercise but not mental stress. The combined effects of TRPV1 rs222747 and BDKRB2 rs1799722 on blood pressure and heart rate responses during exercise were additive, and primarily found in men. Genetic differences in skeletal muscle metaboreceptors may be a risk factor for exaggerated blood pressure responses to exercise. ABSTRACT: Exercise blood pressure (BP) responses demonstrate high inter‐individual variability, which could relate to differences in metabolically sensitive afferent feedback from the exercising muscle. We hypothesized that single‐nucleotide polymorphisms (SNPs) in genes encoding metaboreceptors present in group III/IV skeletal muscle afferents can influence the exercise pressor response. Two hundred men and women underwent measurements of continuous BP and heart rate at baseline and during 2 min of static handgrip exercise (30% maximal volitional contraction), post‐exercise circulatory occlusion and mental stress (serial subtraction; internal control). Participants were genotyped for SNPs in TRPV1 (rs222747; G/C), ASIC3 (rs2288645; G/A), BDKRB2 (rs1799722; C/T), PTGER2 (rs17197; A/G) and P2RX4 (rs25644; A/G). Exercise systolic BP (19 ± 10 vs. 22 ± 10 mmHg, P = 0.03) was lower in GG versus GC/CC minor allele carriers for TRPV1 rs222747, while exercise diastolic BP (14 ± 7 vs. 17 ± 7 mmHg, P = 0.007) and heart rate (12 ± 8 vs. 15 ± 9 beats min(−1), P = 0.03) were lower in CC versus CT/TT minor allele carriers for BDKRB2 rs1799722. Individuals carrying both minor alleles for TRPV1 rs222747 and BDKRB2 rs1799722 had greater systolic (22 ± 11 vs. 17 ± 10 mmHg, P = 0.04) and diastolic (18 ± 7 vs. 14 ± 7 mmHg, P = 0.01) BP responses than those with no minor alleles; these differences were larger in men. No differences in BP or heart rate responses were detected during static handgrip with ASIC3 rs2288645, PTGER2 rs17197 or P2RX4 rs25644. None of the selected SNPs were associated with differences during mental stress. These findings demonstrate that variants in TRPV1 and BDKRB2 receptors can contribute to BP differences during static exercise in an additive manner.